PELATIHAN KOMPUTER KEPADA APARATUR DESA LUMBAN PEA TIMUR - Jamaluddin Jamaluddin; Eviyanti Novita Purba; Roni J. Simamora; Imelda S. Dumayanti; Rimbun Siringoringo; Rena Nainggolan; Alfonsus Situmorang; Posma S. M. Lumbanraja; Apriani M. Sibarani; Arina P. Silalahi; Stevani L. Z. Simanjuntak; Thomson J. Napitupulu (Jurnal Pengabdian Pada Masyarakat METHABDI, 2022)
Community Service is part of the Tridarma of Higher Education. Community Service is oriented to the practice of science and technology directly in the community. The goal is to implement the Tridarma of Higher Education as well as to contribute ideas and transfer technology to the East Lumban Pea Village apparatus. As the application of technology has touched almost all fields of work, including the government sector. This PKM activity was carried out for four days with computer training materials using Google Meet, Zoom, Attandace Tracker and Google Form. This topic is needed to equip village officials to hold meetings and other online activities.